Compensatory Adaptations of Structural Dynamics in an Intrinsically Disordered Protein Complex1. Issue 15 (6th March 2014) - Kurzbach, Dennis; Schwarz, Thomas C.; Platzer, Gerald; Höfler, Simone; Hinderberger, Dariush; Konrat, Robert
Abstract Intrinsically disordered proteins (IDPs) play crucial roles in protein interaction networks and in this context frequently constitute important hubs and interfaces. Here we show by a combination of NMR and EPR spectroscopy that the binding of the cytokine osteopontin (OPN) to its natural ligand, heparin, is accompanied by thermodynamically compensating structural adaptations. The core segment of OPN expands upon binding. This "unfolding‐upon‐binding" is governed primarily through electrostatic interactions between heparin and charged patches along the protein backbone and compensates for entropic penalties due to heparin–OPN binding. It is shown how structural unfolding compensates for entropic losses through ligand binding in IDPs and elucidates the interplay between structure and thermodynamics of rapid substrate‐binding and ‐release events in IDP interaction networks.